The Impact of Migration on Productivity and Native-Born Workers' Training - Francesco Campo; Giuseppe Forte; Jonathan Portes (Institute of Labor Economics (IZA), 2018)
We investigate the relationship between migration and productivity in the UK, using an instrumental variable along the lines suggested by Bianchi, Buonanno and Pinotti (2012). Our results suggest that immigration has a positive and significant impact (in both the statistical sense and more broadly) on productivity, as measured at a geographical level; this appears to be driven by higher-skilled workers. The results for training are less clear, but suggest that higher-skilled immigration may have a positive impact on the training of native workers. We discuss the implications for post-Brexit immigration policy.
Keywords: E24; J24; J61; M53; 330; immigration; productivity; training; Great Britain